RELASI ISLAM DAN NEGARA DALAM RANAH LOKAL (sTudi perda no 1 Tahun 2001 TenTang Visi agaM Madani di kabupaTen agaM) - Syafwan Rozi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2010)
The district regulation (Perda) in the regency of Agam No 1 year of 2001 about the vision of “Agam Madani dan Berprestasi” is a kind of local legislation which has applied the unique relation between Islam and state. The regency of Agam is an important part of the concept of Minangkabau geographical identity. In the vision stated that there is a principle and main basic which is being the main source of Agam society to think, do and act. By using the approach of ethnographic of Spradley, this study is able to answer the problem if the Islamic movement is either a part of a romanticism implication in the past or a movement that is really recording the biggest of Islam to build the social world, though as we know that Indonesia face the problem of multi crisis dimension. There is an assumption that the Islamic movement has been being get contamined by those who has power to dominate Islam. Then, the legislation reputations of Islamic movement are being decreasing in the national system for gradually.